2001
DOI: 10.1117/12.446621
|View full text |Cite
|
Sign up to set email alerts
|

<title>Video imaging measurement of interfacial wave velocity in air-water flow through a horizontal elbow</title>

Abstract: Two-phase flow in pipelines containing elbows represents a common situation in the oil and gas industries. This study deals with the stratified flow regime between the gas and liquid phase through an elbow. It is of interest to study the change in wave characteristics by measuring the wave velocity and wavelength at the inlet and outlet of the elbow. The experiments were performed under concurrent air-water stratified flow in a horizontal transparent polycarbonate pipe of 0.05m diameter and superficial air and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…The liquid film variations shown in these results reveals the fact that it's build up upstream of the bend part is the main reason for slug formation. The results of these simulations are consistent with the findings presented in [1], [3], [4].…”
Section: Wavy Flow Simulationsupporting
confidence: 91%
See 2 more Smart Citations
“…The liquid film variations shown in these results reveals the fact that it's build up upstream of the bend part is the main reason for slug formation. The results of these simulations are consistent with the findings presented in [1], [3], [4].…”
Section: Wavy Flow Simulationsupporting
confidence: 91%
“…In order to qualify the outcomes of the code, simulation results have been compared with the results acquired from three different techniques developed for the same project. These techniques were: 1) High-accuracy pressure sensors used to probe pressure variation along the bend [1]; 2) Fiber optic sensing system (with Laser) used to determine the liquid film thickness and interfacial wave velocity [3]; and 3) High-speed video imaging system developed to determine the interfacial wave velocity [4]. The comparison showed a reasonable agreement.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They observed several flow patterns such as bubbly, dispersed, elongated bubble, slug, stratified, wavy, wavy annular and annular flow patterns. Further studies on advanced photonics measurements can be found in literature [47,[91][92][93][94][95][96][97][98][99][100][101][102][103][104][105] In literature, different flow pattern maps were proposed to predict the two-phase gas/liquid flow regimes. Although in literature these flow maps were investigated for larger length scale experimental set-up, the applicability of these maps to smaller length scale set-up was not conducted extensively.…”
Section: Advanced Photonics and Image Analysis Techniquesmentioning
confidence: 99%
“…They observed several flow patterns such as bubbly, dispersed, elongated bubble, slug, stratified, wavy, wavy annular and annular flow patterns. Further studies on advanced photonics measurements can be found in literature [47,[91][92][93][94][95][96][97][98][99][100][101][102][103][104][105] In literature, different flow pattern maps were proposed to predict the two-phase gas/liquid flow regimes. Although in literature these flow maps were investigated for larger length scale experimental set-up, the applicability of these maps to smaller length scale set-up was not conducted extensively.…”
Section: Advanced Photonics and Image Analysis Techniquesmentioning
confidence: 99%